Style as a Deviation: An Analysis of Stylo-Graphic Idiosyncrasies of Legislative Texts - Ajenifari Joshua Taiwo; Omolade Bamgboye (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
The paper investigates the stylistic peculiarities that are associated with legislative texts. This is done through the purviews of Halliday’s (1971) grapho-stylistics and Mukarovsky’s (1964) concepts of foregrounding and deviation. Legislative proclamations and treaties are veritable and fertile grounds for textual hermeneutics from both linguistic and legal orientations. This present study, however, presents a new frontier as it focuses on the graphological patterning inherent in a selected treaty-based legislative text namely the International Covenant on Economics, Social and Cultural Rights 1976 (ICESCR). The paper finds that stylistic elements at the graphological level are intentionally employed for their inevitability for meaning processing of the text. The resources such as sectionalisation, paragraphing, italicization, synoptic listing/numbering, spacing and other textual arrangement of the document are occasioned for their intended communicativeness rather than for aesthetic glorification. They all perform deliberate stylistic functions of presenting and framing information that conspicuously call the attention of the readers to the intents of the text owing to their unusualness. The researchers recommend that more scholarly efforts be expended on this interesting genre of textual presentation.